2021
DOI: 10.1007/s40475-021-00236-3
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status: Can It Affect the Risk of Infection and the Severity of COVID-19 Symptoms?

Abstract: Purpose of Review In the midst of the COVID-19 pandemic, several academic studies have emerged that explore the importance of vitamin D in the development of the SARS-CoV2 infection. The basis of this interest comes from the established effect vitamin D status has on other acute respiratory infections, such as influenza. This article aims to determine the role and effect of vitamin D serum concentration in the prevalence and severity of COVID-19. Recent Findings Several observational studies have demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
(88 reference statements)
0
4
0
1
Order By: Relevance
“…It played an essential role in macrophage differentiation and modulated the host response against inflammation [ 23 ]. Vitamin D levels can influence the development and severity of acute respiratory infections, such as influenza and acute pneumonia [ 24 , 25 ]. Results from a meta-analysis involving 46 randomized controlled trials showed that vitamin D supplementation demonstrated a protective effect against acute respiratory tract infections [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…It played an essential role in macrophage differentiation and modulated the host response against inflammation [ 23 ]. Vitamin D levels can influence the development and severity of acute respiratory infections, such as influenza and acute pneumonia [ 24 , 25 ]. Results from a meta-analysis involving 46 randomized controlled trials showed that vitamin D supplementation demonstrated a protective effect against acute respiratory tract infections [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ricci et al 26 reported that 80% of their COVID-19 patients had vitamin D deficiency and 6.5% had vitamin D insufficiency. Paiz et al 27 reported that vitamin D has recently become more prominent in studies due to its possible effect on the incidence of COVID-19 infection. Moreover, Ilie et al 22 found that the oldest portion of the population, which is the most susceptible to COVID-19 infection, is also the group with the lowest vitamin D levels.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, there is solid evidence that Vit D supplementation can reduce the rate of infection. For example, it has been shown that Vit D status can impact the development and severity of acute respiratory tract infections, such as influenza and pneumonia [ 208 , 209 ].…”
Section: Vitamin D and Overall Risk Of Infectionmentioning
confidence: 99%